2005
DOI: 10.1128/jvi.79.13.7979-7989.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular Drosophila melanogaster Protein with Similarity to Baculovirus F Envelope Fusion Proteins

Abstract: Baculovirus F (fusion) proteins are found in the envelopes of budded virions. Recently a Drosophila melanogaster gene (CG4715) that encodes a protein with sequence similarity to baculovirus F proteins was discovered. To examine similarities and differences with baculovirus F proteins, we cloned the D. melanogaster cellular F (Dm-cF) protein gene and analyzed Dm-cF expression and localization. The predicted Dm-cF protein sequence lacks a furin cleavage site, and transiently expressed Dm-cF showed no protein cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…(B) An “expected” phylogeny of Drosophila species is shown, summarizing results from many genes [30,31]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) An “expected” phylogeny of Drosophila species is shown, summarizing results from many genes [30,31]. …”
Section: Resultsmentioning
confidence: 99%
“…Compared to mammalian genomes, Drosophila genomes have a higher rate of DNA loss [29], thus proviral sequences are more likely to reflect recent insertion events or insertions that have been selectively retained. In our survey, we unexpectedly found that the D. melanogaster genome contains a host gene, CG4715 (renamed Iris in this paper), which is homologous to the env genes from baculoviruses and insect retroviruses (also identified in [22] [30]). We have now investigated the evolution of Iris in insect genomes, and found it to be conserved in most Drosophila species of the Sophophora subgenus.…”
Section: Introductionmentioning
confidence: 96%
“…There is evidence that several baculovirus genes have been transferred horizontally from eukaryotes, possibly from their hosts or bacterial sources (Hughes & Friedman, 2003). Some genes originally derived from a host may have different functions in the virus due to viral adaptation, as was found recently for the baculovirus F protein (Lung & Blissard, 2005).…”
Section: Shared Orfs Between Nesenpv and Nelenpvmentioning
confidence: 88%
“…It has been postulated that gp64 was acquired during baculovirus evolution (Pearson et al, 2000) and it is established that GP64 is not present in ODV envelopes (Hohmann and Faulkner, 1983;Keddie et al, 1989;Wang and Kelly, 1985). The gp64 gene has a common origin with tick-transmitted mammalian arboviruses (Morse et al, 1992) while the f protein gene has an insect origin (Lung and Blissard, 2005). The different origins of these proteins would influence how they function in the virus.…”
Section: Multiple Occlusion and Bypass Of Midgut Cell Replicationmentioning
confidence: 99%